A Novel Routing Protocol-Based Data Transmission to Enhance the Quality of Service for Internet of Medical Things Using 5G - Zahraa A. Jaaz; Inteasar Yaseen Khudhair; Hanaa M. Mushgil, (International Journal of Interactive Mobile Technologies (iJIM), 2023)
When it comes to improving people's health, various forms of smart city applications are put to use in the area of smart healthcare. Health care providers are increasingly using the internet of medical things (IoMT) as an environment of linked healthcare systems, computational capabilities, and health monitors to improve the quality of service (QoS). Smart healthcare devices transmit data to IoMT and it requires an efficient solution. IoMT's and 5G networks' importance necessitates the development and testing of a novel multi-hop reinforced clustering-based routing protocol (MRCRP) to improve health data transmission's QoS. Cluster head selection is carried out using an energy-efficient approach to enhance resource usage. Min-max normalization is used to transform original data into meaningful data for more analysis. Using principal component analysis (PCA), relevant features can be extracted. The proposed routing technique is then employed to effectively transmit the data. The suggested approach's performance measures, such as delay, throughput, energy consumption, and packet drop ratio are studied, as is a comparative analysis with standard routing protocols..